Sistem Penunjang Keputusan Penerimaan Peserta Didik Baru Jalur Zonasi Dengan Combined Algorithm (Simple Additive Weighting Dan Profile Matching) - Hakim, Bhustomy; Monica Geasela, Yemima; Hansen, Yoel (LPPM Institut Pendidikan Nusantara Global, 2024)
In the 5.0 era, Indonesia has implemented a New Student Admissions (PPDB) system with a zoning policy that selects students based on distance from home as an effort to equalize the quality of education. However, this zoning policy causes many problems, such as fraudulent Family Card falsification to manipulate the distance from home to school, as well as negative impacts felt by the school so that the school cannot control the quality of its prospective students. Students' grades, obedience and fighting power were felt to have decreased compared to students from the year before the zoning policy was introduced. This is a fundamental educational problem. In this research, a combination of decision support system (DSS) algorithms is proposed with the aim of overcoming the problem of student selection which is not only seen from distance to home but also suitability to school criteria, as well as minimizing possible cheating. The algorithm is a combination of the Simple Additive Weighting (SAW) and Profile Matching which finds which prospective students match the school's criteria. The criteria are distance, grades, age and achievements which determine the final grade of each prospective student using the Profile Matching. Each of these criteria is determined from the sub-criteria which are given weights in the SAW accordance with school regulations. By doing so, quality of the school is maintained, and the community can still feel fair about the functioning of the system resulting from the application of technology in this education sector.